2011
DOI: 10.1590/s1519-566x2011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Termites as Bioindicators of Habitat Quality in the Caatinga, Brazil: Is There Agreement Between Structural Habitat Variables and the Sampled Assemblages?

Abstract: The composition of termite assemblages was analyzed in three caatinga sites of the Estação Ecológica do Seridó, located in the municipality of Serra Negra do Norte, in the state of Rio Grande do Norte, Brazil. These sites have been subjected to selective logging, and cleared for pasture and farming. A standardized sampling protocol for termite assemblages (30h/person/site) was conducted between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 13 publications
(23 reference statements)
3
23
0
3
Order By: Relevance
“…In terms of other Brazilian morphoclimatic domains, the number of species encountered here was within the amplitude reported for areas of Cerrado vegetation (30 to 70 species) (Constantino 2005) and for the Amazon region (11 to 88 species) (Bandeira & Macambira 1988, Bandeira 1989, Constantino 1992, De Souza & Brown 1994, but higher than the amplitude reported for Caatinga areas (10 to 26 species) (Mélo & Bandeira 2004, Alves et al 2011.…”
Section: Discussionsupporting
confidence: 70%
“…In terms of other Brazilian morphoclimatic domains, the number of species encountered here was within the amplitude reported for areas of Cerrado vegetation (30 to 70 species) (Constantino 2005) and for the Amazon region (11 to 88 species) (Bandeira & Macambira 1988, Bandeira 1989, Constantino 1992, De Souza & Brown 1994, but higher than the amplitude reported for Caatinga areas (10 to 26 species) (Mélo & Bandeira 2004, Alves et al 2011.…”
Section: Discussionsupporting
confidence: 70%
“…The assemblages of termites include a great relative abundance of H. sulcatus, which appears to be one of the most important species to the wood cycle in dry areas and it is very resistant to disturbance (Alves et al, 2011). Melo and Bandeira (2007) measured the influence of this species in wood consumption in the Caatinga, and found that it was a generalist species that could consume wood in different stages of decomposition, even when already attacked by other species of termites.…”
Section: Discussionmentioning
confidence: 99%
“…The species A. amifer has been recorded in the Caatinga (Alves et al, 2011;Vasconcellos et al, 2010), Atlantic Forest, and Cerrado (Mélo & Bandeira, 2004), and may be considered of wide distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations